2016
DOI: 10.1103/physrevlett.117.044302
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation-Induced Fracture Causes Nanocorrugations in Brittle Metallic Glasses

Abstract: Brittle metallic glasses exhibit a unique and intriguing fracture morphology of periodic nanocorrugations whose spacing and amplitude are of the order of tens of nanometers. We show through continuum simulations that they fail by spontaneous and simultaneous cavitation within multiple weak zones arising due to intrinsic atomic density fluctuations ahead of a notch tip. Dynamic crack growth would then occur along curved but narrowly confined shear bands that link the growing cavities. This mechanism involves li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…As can be seen, discrete cavities nucleate ahead of the crack front, grow with curved sharp tips, and coalesce along an organized path; i.e., an extending tadpole-like curved tip grows from one edge of a cavity and links the other side of the growing cavity ahead of it (see also fig. S3), similar to the inference from simulation (36). It is intriguing to note that there exist nanoscale droplet-like pile-ups surrounding each cavity, corresponding to the white regions in Fig.…”
Section: Observation Of Cavitation-dominated Crack Propagationsupporting
confidence: 81%
See 2 more Smart Citations
“…As can be seen, discrete cavities nucleate ahead of the crack front, grow with curved sharp tips, and coalesce along an organized path; i.e., an extending tadpole-like curved tip grows from one edge of a cavity and links the other side of the growing cavity ahead of it (see also fig. S3), similar to the inference from simulation (36). It is intriguing to note that there exist nanoscale droplet-like pile-ups surrounding each cavity, corresponding to the white regions in Fig.…”
Section: Observation Of Cavitation-dominated Crack Propagationsupporting
confidence: 81%
“…S1B). The above observations explain the longstanding puzzle of how the nanocorrugated fracture morphologies are formed in MGs and clarify that the periodic nanocorrugation patterns are not governed by the fluid meniscus instability or the wavy or oscillatory crack propagation but induced by the ordered cavitation process (24,(32)(33)(34)(35)(36)(37). MGs is also governed by the cavitation mechanism, resulting in the periodic wave-like nanocorrugated morphologies (Fig.…”
Section: Observation Of Cavitation-dominated Crack Propagationsupporting
confidence: 55%
See 1 more Smart Citation
“…Such voids are directly seen in TEM specimen without applying a Fourier analysis and are of a much larger length scale. It was therefore concluded that the formation of a microcrack proceeds via excess free volume coalescence to nanovoids, subsequently growing and thereby leading to microcracks inside the shear band . The formed microcracks were then believed to cause a shear‐band‐to‐crack transition, providing a mechanistic view on how a developed shear band can initiate fracture in an MG.…”
Section: Elastic and Structural Fluctuations Introduced By Deformationmentioning
confidence: 99%
“…Cavitation instabilities may be induced in most forms of matter, e.g. fluids [1,2], polymers [3,4], amorphous solids [5][6][7], deuterated solvents [8], liquid helium [9], biological tissue [10], engineering materials [11], through the rapid deposition of high-intensity energy, e.g. by impact [11], laser irradiation [12], ultrasound [2], hydrodynamic machinery [3], the snapping claw of the Alpheus heterochaelis [13].…”
mentioning
confidence: 99%